Surfactant-assisted incorporation of ZrO2 nanoparticles in quaternized poly(2, 6-dimethyl-1, 4-phenylene oxide) for superior properties of anion exchange membranes. (April 2020) - Yang, Yunfei; Ye, Niya; Chen, Shaoshuai; Zhang, Dengji; Wan, Ruiying; Peng, Xiaomeng; He, Ronghuan
Abstract: Uniformly introducing inorganic additives into polymer matrix could effectively improve the properties of the polymer membranes. Herein, the ZrO2 nanoparticles containing a surfactant cetyltrimethylammonium bromide (CTAB), denoted as sZrO2, were synthesized and used as an additive to prepare anion exchange membranes (AEMs) based on 1-methylpyrrolidinium quaternized poly(2, 6-dimethyl-1, 4-phenylene oxide) (MPPO). The presence of the surfactant effectively improved the compatibility of the inorganic filler and the polymer matrix according to the morphology analysis. Compared to those of the MPPO membrane, the conductivities and tensile strengths of the composite membranes increased by 10–29% and 38–63%, respectively, benefiting from the presence of the sZrO2 and the leave-in surfactant CTAB. A hydroxide conductivity of 88.7 mS cm −1 was achieved in water at 80 °C by the MPPO-1.0 wt%sZrO2 membrane. Moreover, 74.2% of its initial conductivity were retained after immersed the membrane in 1 M KOH at 80 °C for 408 h. This membrane-based single fuel cell exhibited a peak power density of 515.6 mW cm −2 at 60 °C by fueling with humidified H2 and O2 with 0.1 MPa back pressure. More characterizations on the structures of associated materials by using FT-IR, 1 H NMR, TEM, and X-Ray Diffraction were made as well. Graphical abstract: Image 1 Highlights: Uniformly disperse ZrO2 nano particles in polymer membranes assisted by a surfactant. Concurrently achieving enhanced ionic conductivity and tensile strength of the membranes. Improved tolerance to alkali of the prepared composite membranes. The proposed membrane based single cell exhibits a peak power density of 515.6 mW cm −2 .